Geographic variation in forest composition and precipitation predict the synchrony of forest insect outbreaks. Issue 4 (4th December 2017) - Haynes, Kyle J.; Liebhold, Andrew M.; Bjørnstad, Ottar N.; Allstadt, Andrew J.; Morin, Randall S.
Abstract : Evaluating the causes of spatial synchrony in population dynamics in nature is notoriously difficult due to a lack of data and appropriate statistical methods. Here, we use a recently developed method, a multivariate extension of the local indicators of spatial autocorrelation statistic, to map geographic variation in the synchrony of gypsy moth outbreaks. Regression analyses indicated that local synchrony of gypsy moth defoliation increased with the local synchrony of precipitation and the proportion of host tree density composed of oaks, especially those in the Lobatae (red oak) section. This may be the first study that demonstrates a relationship between defoliator population synchrony and host tree composition. More broadly, this study contributes to a small body of recent work that illustrates how mapping hotspots of unusually high or low synchrony facilitates an improved understanding of factors influencing spatially synchronous population dynamics generally, and triggers of pest insect outbreaks, more specifically.